Respon beberapa varietas padi gogo (Oryza sativa L.) unggul pada kondisi tegangan air yang berbeda di media tanah Ultisol - Muhamad Rasyid; Syafrinal Syafrinal; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research was conducted in the greenhouse of Faculty of Agriculture, University of Riau, Pekanbaru from February to July 2016. The experiment used a completely randomized design (CRD), factorial and 3 replications. The first factor:soil water tension, consists of three levels (pF 1.00 to 1.97, pF 2.29 to 2.54 and pF 2.70 to 3.00) and the second factor: upland rice varieties which consists of three varieties (Situ Patenggang, Situ Bagendit, and Inpago 8). The data were statistically analyzed by ANOVA and Duncan test continued level of 5%. Parameters measured were plant height, plant growth rate, the maximum number of tillers, the number of productive tillers, harvesting, root volume, the ratio of the canopy and roots, crop straw weight, weight of 100 grains, pithy grain percentage, and the weight of dry milled grain. The results showed the interaction soil water tension and varieties of upland rice significantly affected the rate of plant growth, the number of maximum tillering, the number of productive tillers, harvesting, root volume, heavy crop straw, weighting 100 grains, the percentage of pithy grain, and the weight of grind dry grain. The combination of soil water tension pF 1.00 to 1.97 and varieties Situ Bagendit is the best combination, because the weight of dry milled grain yield tends more. Keywords:superior upland rice varieties, soil water tension, Ultisol.